Use of angiotensin II receptor blockers in children- a review of evidence - Nwaiwu O; Olayemi SO; Amao O (Nigerian Journal of Paediatrics, 2024)
Background: The incidence of hypertension in the pediatric population has been increasing. Childhood blood pressure is predictive of adult BP. The renin angiotensin aldosterone system pathway is important in the mediation of pediatric hypertension. New therapies approved for adults are often used off label in children with little or no efficacy and safety data in the paediatric population The angiotensin receptor blockers has been shown to be effective and safe in the treatment of pediatric hypertension. Objective: The objective of this review is to hig hlight available clinical evidence on the efficacy, safety tolerability and kinetics of angiotensin receptor blockers in childhood hypertension and its antiproteinuric effect in renal disease.